BACTERIOLOGICAL & SEROLOGICAL STUDY OF BRUCELLOSIS IN BUFFALO IN BAGHDAD: S.A. Al-Bayatti ; A.N. Al-Thwani ; S.A. Al-ammaraie and A.A. Haddi - Al-Bayatti, S. A. (The Iraqi Journal of Veterinary Medicine, 2006)
To study the prevalence of brucellosis among buffalo in Baghdad, 144serum samples were collected and tested serologically using Rose Bengal PlateTest (RBPT) and Tube Agglutination Test (TAT), also 44 milk samples testedby Milk Ring Test (MRT). For isolation and identification of Brucella speciesand behavior, 15 buffalo aborted fetuses were used. And for evaluation of thehealth hazzard caused by the consumption of the locally manufactured creamfrom the milk of buffalo, 76 cream samples were used for cultivation.The results of the RBPT, TAT and MRT revealed the prevalence of thedisease in the percentages (38.19%, 29.86% and 20.45%) respectively.It was found that Brucella abortus was the main cause of abortion in thebuffalo (53.33%). There biotypes were the 8th and 3rd.The cream samples manufactured from the milk of buffalo doesn’t showhealth hazzard as a cause of brucellosis in human, because it didn’t revealed anyBrucella isolates in all samples used.